Analytical and experimental investigation of grinding fluid hydrodynamic pressure at wedge-shaped zone. (1st January 2011) - Li, C.H.; Hou, Y.L.; Fang, Z.; Ding, Y.C.
The conventional method of delivering grinding fluid with a high supply of pressure and hydrodynamic fluid pressure can be generated ahead of the contact zone due to the wedge effect. In the present paper, theoretical hydrodynamic pressure modelling was applied to induce a flow of coolant fluid through the grinding zone during flood delivery grinding. The simulation results show that hydrodynamic pressure was proportional to grinding wheel velocity, and inversely proportional to the minimum gap between the wheel and workpiece surface. The maximum pressure value was generated in the minimum gap region where higher fluid pressure gradient occurred. Moreover, the hydrodynamic pressure at the wedge-shaped zone was also measured through experiments. The results suggest that the proposed model agrees with the theoretical model and it can accurately forecast changes in the hydrodynamic pressure at the contact zone between the grinding wheel and the workpiece.